Generic structure and promotional elements in best-selling online book blurbs: a cross-cultural study - Neslihan Önder (Ibérica, 2013)
This study investigates the generic structure and promotional elements of the online fiction blurbs accompanying the 95 best-selling books from Amazon United Kingdom and Okuoku Turkey (1999-2011), a company that sells books online that are written in Turkish or translated into Turkish, and adds to the growing number of investigations into this genre (Kathpalia, 1997; Bhatia, 2004; Cacchiani, 2007; Gea-Valor, 2007; Gesuato, 2007; Basturkmen, 2009). Based on the findings, a two-level schematic structure (moves and steps) is proposed for the blurbs following Swales (1990). The findings suggest that Amazon UK book blurbs have a six-move schematic structure: complimenting the author, book description, justifying the book by establishing a niche, book promotion, author’s background and author’s website/blog being the second, fourth and fifth obligatory moves. However, Okuoku book blurbs feature a five-move schematic structure with complimenting the author, book description, involving the reader in the text, book promotion and author’s background, the second and fourth being obligatory. Analysis of promotional elements in the corpora reveals that online fiction book blurbs employ the art of advertising through the use of favorable expressions (Bhatia, 2005) and innovative uses of rhetorical strategies to persuade the reader to read the book.